A comparison between rare earth and transition metals working as magnetic materials in an AMR refrigerator in the room temperature range. (5th December 2015) - Aprea, C.; Greco, A.; Maiorino, A.; Masselli, C.
Abstract: This paper describes a two-dimensional (2D) multiphysics model of a packed bed regenerator made of magnetocaloric material. The regenerator operates as a refrigerant for a magnetic refrigerator operating at room temperature on the strength of an active magnetic regenerator (AMR) cycle. The model is able to simulate the thermofluidodynamic behavior of the magnetocaloric material and the magnetocaloric effect of the refrigerant. The model has been validated by means of experimental results. Different magnetic materials have been tested with the model as refrigerants: pure gadolinium, second order phase magnetic transition Pr0.45 Sr0.35 MnO3 and first order phase magnetic transition alloys Gd5 (Si x Ge1− x )4, LaFe11.384 Mn0.356 Si1.26 H1.52, LaFe11.05 Co0.94 Si1.10 and MnFeP0.45 As0.55 . The tests were performed with fixed fluid flow rate (5 l/min), AMR cycle frequency (1.25 Hz) and cold heat exchanger temperature (288 K) while the hot heat exchanger temperature was varied in the range 295–302 K. The results, generated for a magnetic induction which varies from 0 to 1.5 T, are presented in terms of temperature span, refrigeration power and coefficient of performance. From a global point of view (performances and cost), the most promising materials are LaFeSi compounds which are really cheaper than rare earth compounds and they give a performance sufficiently higher than gadolinium. Graphical abstract: Active Magnetic Refrigeration (AMR) cycle; First Order Transition magnetic materials (FOMT); Second Order Transition magnetic materials (SOMT) Highlights: Comparison between different magnetic materials. 2D model of an Active Magnetic Regenerative refrigeration cycle. Validation of the model with experimental data. Gd5 (Si x Ge1− x )4 is the most performant magnetic material. The most promising are LaFeSi compounds which are cheaper and they give high performances.